Efficient UWB filter design technique for integrated passive device implementation. Issue 14 (1st July 2015) - Saadi, A.A.; Yagoub, M.C.E.; Touhami, R.; Slimane, A.; Taibi, A.; Belaroussi, M.T.
Abstract : A new approach is proposed to act as an efficient design technique for the implementation of ultra‐wideband (UWB) bandpass filters in integrated passive device technology. The proposed design is based on two major original contributions. First, the use of hourglass filter theory which, to the best of authors knowledge, has not been applied yet to such technology. Then, the minimisation of the number of inductors involved in the filter circuit through the zigzag technique. Implemented in 0.18 µm CMOS technology, the designed filter exhibits excellent performances such as two finite tunable transmission zeros, enhanced selectivity, a bandwidth covering the entire UWB spectrum of 3.1–10.6 GHz, a stopband rejection better than 15 dB throughout frequencies below 2.7 GHz and above 11 GHz, a good matching better than 11 dB, a minimum mid‐band insertion loss of 1.8 dB and, finally, a sufficiently constant group delay. With these features and only 10 lumped elements, the proposed filter is one of the most promising compact filters for UWB applications.